Is Nebivolol Really Effective in Preventing Contrast Induced Nephropathy? - Orcun Altunoren; Mehmet Balli; Necmi Eren; Hakan Tasolar; Abdullah Arpaci; Caglar Emre Caglayan; Yasemin Coskun Yavuz; Ozkan Gungor (Karger Publishers, 2015)
Background/Aims: Contrast induced nephropathy (CIN) has multifactorial etiopatogenesis including oxidative stress and vasoconstriction. Nebivolol is an antioxidant and has vasodilatatory effect via NO release and may prevent CIN development. We have noticed that a few number of studies that have evaluated the effectiveness of nebivolol for the prevention of CIN used serum creatinine (sCr) levels for CIN detection. However, sCr is an insensitive marker for renal damage. Therefore in this study we used serum neutrophil-gelatinase associated lipocalin (NGAL), a more sensitive marker of renal damage, to evaluate preventive role of nebivolol in CIN. Methods: 159 patients undergoing coronary angiography (CAG) who had at least one risk factor for CIN were divided into nebivolol (+) and (-) groups. CIN was defined as a rise in sCr of 0.5mg/dl or a 25% increase from the baseline value. Serum Cr, glomerular filtration rate (eGFR) and NGAL levels were assessed before and 48 h after CAG. Mehran risk scores were calculated for both groups. Results: Both groups were similar in terms of baseline characteristics, Mehran risk scores, and current medications. Clinically, CIN developed at similar rates in both groups. Serum Cr, eGFR and NGAL values were similar in both groups before and after CAG. Serum Cr and NGAL levels increased and eGFR decreased significantly compared to the levels before CAG. Patients who developed CIN were significantly older (p=0.003), and were more likely to have DM (p=0.012), a higher mean contrast agent volume (pConclusion: According to the results of our study Nebivolol does not seem to prevent CIN in patients undergoing CAG. However, further randomised controlled trials with more sensitive renal damage markers are obviously needed to understand the actual effect of nebivolol on CIN especially through oxidative pathways and in high risk patients.